2015
DOI: 10.1179/2045772315y.0000000042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety and reliability of the newly-proposed AO spine injury classification system

Abstract: Objective: To evaluate the safety and reliability of the new AO Classification, a recent classification system for Thoraco-Lumbar Spine Trauma (TLST). Design: Retrospective study. Methods: We applied the new AO system in patients with TLST treated according to the TLICS. Two researchers classified injuries independently. Eight weeks later, the classification was repeated for intra and inter-observer agreement evaluation. To evaluate safety, we correlated the treatment performed based on the TLICS with the newe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
9
0
3
Order By: Relevance
“…The literature search identified 63 unique records, of which 17 were selected for the full-text review and 9 articles 3,20-27 were included in the final review (Figure 1). There was a substantial variation in the characteristics of included studies in terms of the number of observers and cases and imaging modalities (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 63 unique records, of which 17 were selected for the full-text review and 9 articles 3,20-27 were included in the final review (Figure 1). There was a substantial variation in the characteristics of included studies in terms of the number of observers and cases and imaging modalities (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…16 The new morphological classifications based on these mechanisms proposed by AOSpine, [15][16][17] both of the subaxial cervical and thoracolumbar spines, were assessed by the authors and were shown to be reproducible and safe in the series evaluated. [18][19] Additionally, fractures can usually be classified as either stable or unstable. The concept of stability was defined by White and Panjabi 20 as the capacity of the spine to maintain alignment under physiological loads, without pain or neurological injury.…”
Section: Discussionmentioning
confidence: 99%
“…The spino-pelvic relationships evaluated, the final global spinal alignment, LL, and TK did not associate with outcome measures (ODI and SF 36 physical status) ( Table 3 and 4). Furthermore, while the study is undoubtedly limited because of the small size, the results of this study did not even find a trend; therefore, it is likely that these results truly represent no correlation and are not just the result of an underpowered study.…”
Section: Discussionmentioning
confidence: 61%
“…3 While there is no universally accepted treatment algorithm for A3 (burst fractures involving the posterior vertebral wall and a single endplate) and A4 fractures (burst fractures involving the posterior vertebral wall and both endplates), most commonly type A injuries without neurological deficits may be managed without surgery, with a low ris\k of late neurological deterioration. 2,4,5 While the short-term results of nonsurgical fracture management are known, the long-term outcomes of such treatment remain uncertain. 1 Nonsurgical treatment may yield residual deformity which, in turn, may lead to sagittal imbalance, pain, or functional disability.…”
Section: Introductionmentioning
confidence: 99%